Jenis-Jenis Kumbang Tinja (Coleoptera: Scarabaeidae) di Hutan Pendidikan dan Penelitian Biologi (HPPB) Universitas Andalas, Padang - Yuliana Indah Sari; Dahelmi Dahelmi; Henny Herwina (Universitas Andalas, 2015)
A study about dung beetles species was conducted at the Educational and Biological Research Forest. Pitfall trap method was used to collect dung beetles which cow, cat and human feses were put above each of the trap. The beetles colection was conducted at four locations (river, permanent plot, camp and villa). A total of 10 species of dung beetles that belong to two subfamilies, three tribes and five genera was collected. About three species were not reported in previous studies in West Sumatra.Keywords: Coleoptera, Scarabaeidae, Pitfall trap, West Sumatera